To Study the Relationship between Psychology and Literature (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The interplay between psychology and English literature offers profound insights into the human condition, exploring the complex layers of human emotions, motivations, and behavior. From the introspective soliloquies of Shakespearean tragedies to the modernist exploration of consciousness in Virginia Woolf’s and James Joyce’s works, literature reflects the depth of human psyche and the influence of inner struggles on external actions. Both the interior workings of the mind and its outward manifestations are included under the broader field of psychology Examining literary and cultural expressions from other countries, languages, and academic fields has been a challenging and sluggish path for the field of comparative literature. we can understand the many issues that plagued Victorian society as a result of the Industrial Revolution, which transformed England from an agricultural to an industrial powerhouse.